The Construction of Traumatic Marriage Reality in Early Adults in Medan City Post-Parental Divorce in the Context of Interpersonal Communication - Adiba, Fairuz Raniah Adiba Putri; Kurniawati, Dewi; Nurbani, Nurbani (Lafadz Jaya Publisher, 2024)
This study analyzes the construction of traumatic marriage reality in early adulthood in Medan City following parental divorce, focusing on intrapersonal communication. The research also explores the forms of traumatic marriage experiences in this context. The study employs the theories of reality construction, family communication, intrapersonal and interpersonal communication, reasoned action, social judgment, trauma, marriage, divorce, and early adulthood. Using a constructivist paradigm and qualitative descriptive method, the study involved five informants: two aged 24, two aged 25, and one aged 19. The results reveal that four informants construct marriage as complex, burdensome, and not a life goal, while one informant shifted from subjective to objective reality, viewing marriage as a source of happiness and a life goal. Three informants experienced complex marriage trauma, while two experienced simple trauma. Interestingly, not all informants with negative marriage constructions experienced complex trauma. Specifically, informants NA, AAP, and AN had negative constructions with complex trauma; informant VWY had negative constructions with simple trauma; and informant HS had a positive construction with simple trauma. This study highlights the diverse ways early adults in Medan City construct and experience the reality of marriage after parental divorce.